Penggunaan kombinasi Gonadotropin untuk pengobatan hipofungsi ovarium pada sapi perah - Masruro, Novia Alfi; Mulyati, Sri; Madyawati, Sri Pantja; Samik, Abdul; Ratnani, Hermin; Harijani, Nenny (Ovozoa: Journal of Animal Reproduction, 2020)
This case report aims to determine the response of estrus and pregnancy rates in dairy cows with ovarian hypofunction by administering a combination of gonadotropin hormones. The sample used was ten dairy cows that had been calving, were not pregnant, showed no signs of estrus for more than 60 days after the last calving and had ovarian hypofunction based on rectal palpation. All dairy cows were injected 300 IU PG-600, then divided into two groups, each injected with 100 and 300 IU hCG respectively for first group and second group, intramuscularly at the time of insemination. The results showed that the estrus response occurred in all cows, in 6-8 (6.8 ± 0.84) days (first group), and 6-7 (6.2 ± 0.45) days (second group). Trans-rectal palpation pregnancy diagnosis 60 days after artificial insemination showed that all dairy cows in both groups were pregnant. It could be concluded that the treatment of dairy cows suffering from ovarian hypofunction with a combination of 300 IU PG-600 and 100 IU hCG was sufficient to induce 100% estrus rates and 100% pregnancy rates.